Penerapan Inovasi dan Kreativitas bagi pengusaha UMKM Berbasis Manajemen Dan Ekonomi Syariah - Rismayanti Bintang; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Micro, small and medium enterprises (SME) engage in entrepreneurship on a smaller or simpler scale. This his SME places great emphasis on creativity and innovation in practice. SMEs (micro, small and medium enterprises) are enterprises that play an important role in the development of the national economy, but are also affected by the COVID-19 pandemic spreading in Indonesia. In Islam, creativity and innovation are also linked with devotion to individuals as economic agents. , leading to positive economic activity. Reverence for God makes a person more productive. This is consistent with human efforts to allocate and manage resources to achieve farah (success) based on the principles and values ​​of the Koran and Sunnah. When running a small business, there are still many obstacles to small business success, including: Limited ability to innovate, poor human skills, and poor financial management. This study therefore provides an opportunity to apply innovation and creativity based on Sharia economics and Sharia management. Public. A qualitative approach was used in this study. The purpose of the qualitative approach is to test and analyze innovation and creativity management of SMEs based on Medan Shariah. The data collection technique used in this study is a survey technique.